Rapid antiretroviral therapy initiation and its effect on treatment response in MSM in West Africa - (:unkn) unknown (My University, 2021)
Objective: To assess the time from HIV diagnosis to ART initiation and the effect of rapid ART initiation (i.e. within 7 days of HIV diagnosis) on attrition and virologic and immunologic responses among MSM in Burkina Faso, Côte d'Ivoire, Mali, and Togo.Design: Prospective cohort study between 2015 and 2019.Methods: MSM aged 18 years or older newly diagnosed with HIV infection were eligible to participate. ART was proposed to participants upon HIV diagnosis, irrespective of clinical stage and CD4+ cell count, and was initiated as soon as possible, with no specific time frame. Determinants of rapid ART initiation and its effect on treatment outcomes were assessed using multivariate analyses.Results: Of 350 MSM, 335 (95.7%) initiated ART after a median time of 5 days. Of the latter, 216 (64.5%) had rapid ART initiation. The 335 participants were followed up for a median time of 24.1 months. One hundred and eleven (33.1%) were not retained in care. Rapid ART initiation was less likely in participants with a CD4+ cell count at least 200 cells/μl [adjusted odds ratio (aOR) 0.37, 95% confidence interval (CI) 0.15-0.88]. It improved viral load suppression (aOR 6.96, 95% CI 1.98-24.46) but had no effect on attrition (aOR 0.87, 95% CI 0.57-1.33) or CD4+ cell count increase (adjusted coefficient 28.23, 95% CI -17.00 to 73.45).Conclusion: These results in MSM in West Africa support the WHO recommendation for rapid ART initiation. Clinics need to develop context-specific strategies for rapid ART initiation and for retaining MSM in HIV care.ClinicalTrials.gov, number NCT02626286.
Keywords: African Research